Pelaksanaan Layanan Bimbingan Kelompok Untuk Meningkatkan Disiplin Belajar Peserta Didik: Implementation Of Group Guiding Services To Improve Discipline Learning Students - Anita Anita; Mohammad Fatchurahman (Suluh: Jurnal Bimbingan dan Konseling, 2018)
The purpose of this study was to improve students' learning discipline at MTs Miftahul Jannah Palangka Raya by using group guidance services. The population in this study amounted to 32 students. The number of research samples consisted of 8 students. Sampling is determined by Random Sampling technique. Data collection techniques use observation, interviews, and the scale of learning discipline. The method used is pre-experiment, the technique of collecting data using the Paired-Sample T Test formula or better known as Pre-Post Design is an analysis involving two measurements on the same subject against a particular influence or treatment. The results of the study show that: based on analysis with Paired-Sample T-Test, it shows that students' learning discipline has an initial average increase of 130.13 to 234.13. This means "Group Guidance Services Can Improve Learning Discipline of Students at MTs Miftahul Jannah Palangka Raya 2016/2017 Academic Year". The results of the analysis show that the eight students in the research subject experienced an increase in learning discipline after the intervention.